Differences in ICU Outcomes According to the Type of Anticancer Drug in Lung Cancer Patients - Hong, Yoonki; Hong, Ji Young; Park, Jinkyeong (Frontiers in Medicine, 2022)
Purpose We investigated the intensive care unit (ICU) outcomes of patients who used targeted therapy compared to those who received cytotoxic chemotherapy. Materials and Methods This study was based on Korean administrative health insurance claims from 2015 to 2019. We extracted data on lung cancer patients (>18 years old) who were admitted to the ICU after receiving chemotherapy. Results 6,930 lung cancer patients who received chemotherapy within 30 days before ICU admission were identified; the patients received cytotoxic chemotherapy (85.4%, n = 5,919) and molecular targeted therapy (14.5%, n = 1,011). Grade 4 neutropenia was identified only in the cytotoxic chemotherapy group (0.6%). Respiratory failure requiring ventilator treatment was more common in the cytotoxic chemotherapy group than in the targeted therapy group (HR, 3.30; 95% CI, 2.99–3.63), and renal failure requiring renal replacement therapy was not significantly different between the two groups (HR, 1.57; 95% CI, 1.36–1.80). Patients who received targeted chemotherapy stayed longer in the ICU than the cytotoxic chemotherapy. The 28-day mortality was 23.4% (HR, 0.79; 95% CI, 0.67–0.90, p < 0.05) among patients who received targeted agents compared with 29.6% among patients who received cytotoxic chemotherapy. Conclusion Targeted chemotherapy for lung cancer may contribute to increasing access to critical care for lung cancer patients, which may play a role in improving critical care outcomes of lung cancer patients.